2007
DOI: 10.1016/j.intacc.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Attribute differences between U.S. GAAP and IFRS earnings: An exploratory study

Abstract: With the successful completion of the IASC's standards, IFRS and US GAAP were placed as the two pre-eminent world financial reporting frameworks. For years, however, US GAAP was accepted widely as the international set of standards to ensure high quality financial statements. Especially in the US, but also elsewhere, the introduction of IFRS has lead to a discussion on the (relative) quality of both regimes. However, relatively little research has been devoted to the subject. In this study, we address that voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(20 citation statements)
references
References 46 publications
2
13
0
5
Order By: Relevance
“…Since prior research on the effects of IFRS on earnings quality leads to contradictory conclusions and given that they depend on country specific and institutional factors, solid conclusions in a different context can not be drawn (van der Meulen et al, 2007).…”
Section: Ifrs and Earnings Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Since prior research on the effects of IFRS on earnings quality leads to contradictory conclusions and given that they depend on country specific and institutional factors, solid conclusions in a different context can not be drawn (van der Meulen et al, 2007).…”
Section: Ifrs and Earnings Qualitymentioning
confidence: 99%
“…Additionally, Jeanjean, and Stolowy (2008) found that IFRS adoption did not have an effect on earnings management in some countries and in specific situations earnings management even increased. There is even evidence that US GAAP provides higher quality reporting information compared to IFRS (van der Meulen et al, 2007). Opponents of IFRS adoption for the foreign issuers also argue that by using IFRS in the US, the comparability of financial statement information furthermore decreases.…”
Section: Consequences Of Ifrs Adoption: Foreign Issuersmentioning
confidence: 99%
See 1 more Smart Citation
“…Macías and Muiño (2011) state that adoption of IFRS in these countries are mostly for satisfying regulatory needs and not for satisfying investors' and creditors' needs. Van der Meulen et al (2007) investigated the attribute differences (value relevance and timeliness) between US GAAP and IFRS earnings. They found that US GAAP and IFRS only differ with regard to the predictive ability as US GAAP outperforms IFRS in given controlling differences.…”
Section: Previous Studies Related To Impact Of Ifrs On Value Relevancmentioning
confidence: 99%
“…(Flower, 1997;Zeff, 1998;Ball, 2001;Hope, 2003;Hope et al, 2006;Meulen et al, 2007;Ding et al, 2007;Soderstrom & Sun, 2007;Barth et al, 2008;Clacher, Ricqebourg, & Hodgson, 2013).…”
Section: Resultsunclassified